Comparison of jumping-landing mechanics of elite handball and wrestling athletes - Tas, B.; Akalp, U.; Kaya, O.; Bingul, B. M. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2025)
Background. Examining and detecting the causes of injuries offers important contributions to athletes. Identifying the risk of non-contact injury in athletes and then directing them to preventive exercise programs may be beneficial for athlete health.